2022
DOI: 10.35808/ijeba/782
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Entrepreneurial Skills on Organizational Performance of Small and Medium Enterprises in Nakuru City-Kenya

Abstract: Purpose: Entrepreneurial skills influence the performance of Small and Medium Enterprises in Kenya. The low business performance of SMEs in Kenya may be attributed to weak managerial and technological, low market share, the shortage of capital, the narrow range of the market. One of the ways of tackling the poor performance of SMEs is improving their entrepreneurial skills. The purpose of research is to determine how entrepreneurial skills influence the level of performance of SMEs in Kenya. Design/methodology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Research by Setiadi (2021) also found that each individual's entrepreneurial skills can improve the business performance of coffee shops in Malang City. Likewise, research results from (Albanus et al, 2022) found a positive influence between entrepreneurial skills and the performance of SMEs in Nakuru City-Kenya. It is also supported by research conducted by (Mustapha et al, 2020), which found that high entrepreneurial ability can bring a business towards progress and success.…”
Section: Relationship Between Entrepreneurial Skills and Smes Perform...mentioning
confidence: 89%
“…Research by Setiadi (2021) also found that each individual's entrepreneurial skills can improve the business performance of coffee shops in Malang City. Likewise, research results from (Albanus et al, 2022) found a positive influence between entrepreneurial skills and the performance of SMEs in Nakuru City-Kenya. It is also supported by research conducted by (Mustapha et al, 2020), which found that high entrepreneurial ability can bring a business towards progress and success.…”
Section: Relationship Between Entrepreneurial Skills and Smes Perform...mentioning
confidence: 89%
“…The results show a very weak relationship between entrepreneurial skills and business performance. Mutuku, Kiilu, Mathuku & Auka (2022) investigated the effect of entrepreneurial skills on the performance of Small and Medium Enterprises in Kenya. Data for this study were collected from a sample of 20 small and medium-sized enterprises using a correlational survey design.…”
Section: Skill Buildingmentioning
confidence: 99%
“…There are many variables that influence the performance of small and medium enterprises, entrepreneurship, workforce skills, infrastructure, finance, leadership skills (Abebaw, Mulate & Nigussie, 2018), and innovation (Iqbal & Yuliandari, 2019) entrepreneurial characteristics (Indarto & Santoso, 2020), entrepreneurial orientation and market orientation (Septrizola, 2021), Entrepreneurial Orientation and skills (Zaato et al, 2020), entrepreneurial skills (Mutuku et al, 2022), entrepreneurial orientation and religiosity (Sefnedi & Yadewani, 2022), human resource skills and capabilities (Wijaya, Yadewani & Karim, 2022), quality of business strategy, ethical seller behavior, process innovation, entrepreneurial orientation perspective, business environment adaptability, and partial competitive advantage ( Asyhari, Pudjihastuti & Kurdaningsih, 2018) skills and experiences (Yadewani, 2023) knowledge and government policies (Yadewani et al, 2023a), innovation and technology (Yadewani et al, 2023b), According to Aliyu and Rosli (2014), trials are considered to be trials in which a small-scale study is conducted before the actual full-scale study. A pilot study was carried out with the goal of achieving numerous objectives.…”
Section: Introductionmentioning
confidence: 99%